2016
DOI: 10.1186/s12884-016-0810-6
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in women who were exposed to domestic violence during pregnancy

Abstract: BackgroundQuality of life in pregnant women is an important issue both for women’s and fetus’ health. This study aimed to examine quality of life in a group of women who were exposed to domestic violence during pregnancy.MethodsThis was a cross sectional study of quality of life among a consecutive sample of pregnant women attending to a teaching hospital in Lorestan, Iran. Women were screened for experiencing violence using the Abuse Assessment Screen (AAS) questionnaire and were categorized as psychological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
48
1
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(63 citation statements)
references
References 38 publications
8
48
1
6
Order By: Relevance
“…Reid et al reported the lowest score in Vitality (12) which is in contrast to our results. Our findings showed lower MSC scores compared with the PSC scores, which is in agreement with the results of previous research (20). Although the mental score of SF 36 concentrates more on depression, anxiety is a main factor in asthma attacks (19).…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…Reid et al reported the lowest score in Vitality (12) which is in contrast to our results. Our findings showed lower MSC scores compared with the PSC scores, which is in agreement with the results of previous research (20). Although the mental score of SF 36 concentrates more on depression, anxiety is a main factor in asthma attacks (19).…”
Section: Discussionsupporting
confidence: 83%
“…In our study, the highest score was observed in Physical Pain domain and the lowest score in Emotional Role functioning. Due to the type of (12,20). Reid et al reported the lowest score in Vitality (12) which is in contrast to our results.…”
Section: Discussioncontrasting
confidence: 57%
See 2 more Smart Citations
“…[2][3][4][5] Reported IPV prevalence is higher than many common obstetric conditions. [6][7][8][9][10][11] Does IPV also put infants at risk through avoidance of breastfeeding? 12 Literature on the effects of IPV during pregnancy on breastfeeding is sparse and has inconsistent results.…”
Section: Introductionmentioning
confidence: 99%